Minat Belajar dengan Penggunaan Media Audio Visual pada Pembelajaran IPAS Kelas V SDN Gunungmulyo Kecamatan Sarang Kabupaten Rembang - Ilmi, Ana Khofidhotun; Ismaya, Erik Aditia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The use of audio-visual media in social studies learning can affect students' interest in learning. Students' interest in learning social studies is influenced by various factors including the application of social studies, learning motivation, student attention, perception of teachers, influence of peers, sources of information, perception of social studies, and learning facilities. This study aims to investigate the role of audio-visual media in influencing learning interest in science subjects at SDN Gunungmulyo, Sarang District, Rembang Regency. The research method used is qualitative with a case study approach. The research subjects were class V students who were selected using purposive sampling techniques. Data collection techniques include observation, documentation, and interviews. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study show that the use of audio-visual media in learning can affect students' interest in learning. Audio-visual media can help students better understand the concept of IPAS, make learning more interesting, and student activeness in the involvement of the learning process. However, the use of video-type audio-visual learning media has supporting and inhibiting factors. Its use can increase students' interest in learning in science subjects, but it takes a long time to make and students may face difficulties in understanding the material.